HISTORICAL HIGHLIGHTS OF THE CAMPAIGN FOR A FIRE-SAFE CIGARETTE (Tufts Archival Research Center, 2007)
Document listing the highlights in the history of the fire safe cigarette. Contains major bills enacted and statements made by officials. Lists states that have held hearings on fire safe cigarette legislation.